Exploring a shift in teacher practices after going through an intervention on the integration of local knowledge in grade 9 physical science lessons - Mika, Rauha T (Rhodes University, Faculty of Education, Department of Education, 2019)
It has been advocated by many scholars that the integration of local or indigenous knowledge into science classrooms might make science more relevant and accessible to learners, particularly in culturally diverse classrooms. As a result, the Namibian Grade 9 Physical Science curriculum expects teachers to integrate learners' local or indigenous knowledge in their science classrooms. Despite these ideals, there are no clear instructions on how to go about doing this. This is exacerbated in part by the poor or lack of continuing professional development for science teachers. It is against this background that this study sought to explore an intervention on the integration of local or indigenous knowledge in Grade 9 Physical Science lessons. The study is underpinned by an interpretive paradigm and is informed by Vygotsky's socio-cultural theory and Wenger's community of practice. Within the interpretive paradigm, a qualitative case study approach was employed. It was carried out in four schools with four Physical Science teachers from Otjiwarongo circuit in Namibia. Qualitative data were generated using workshop discussions, document analysis, semi-structured interviews, classroom observations and reflections. A variety of data generation techniques were used for triangulation and validity purposes. Data were subsequently analysed inductively to come up with themes. The findings of the study revealed that before the intervention the teachers involved in this study had little knowledge about the integration of local or indigenous knowledge in science lessons. However, after their voluntary participation in the intervention, they were enabled to develop and mediate model lessons that integrated local or indigenous knowledge in their classrooms which their learners subsequently found to be stimulating. The findings of the study further revealed that integrating local or indigenous knowledge in science lessons had the potential to promote active participation by learners and foster learning using easily accessible resources. The study thus recommends that teachers should, where possible, strive to integrate learners' local or indigenous knowledge in science lessons.
Keywords: Physical sciences -- Study and teaching (Secondary) -- Namibia; Ethnoscience -- Study and teaching -- Namibia; Science -- Study and teaching (Secondary) -- Namibia; Curriculum planning -- Study and teaching -- Namibia